Permethrin Resistance in Aedes aegypti (Linnaeus) Collected from Kuala Lumpur, Malaysia - Wan-Norafikah, O.; Nazni, W.A.; Lee, H.L.; Zainol-Ariffin, P.; Sofian-Azirun, Mohd (2010)
Permethrin resistance status of a laboratory strain, a permethrin-selected strain and three field strains of Aedes aegypti collected in Kuala Lumpur, Malaysia were evaluated using three standard laboratory bioassays: WHO larval bioassay, WHO adult mosquito bioassay, and mixed function oxidase (MFO) enzyme microassay. The LC50 values of field strains from the WHO larval bioassay did not differ significantly. The highest LC50 value was from the Taman Melati field strain (0.39mg/L). The resistance ratio for the permethrin-selected strain and the field strains ranged from 1.86 fold to 5.57 fold. Pre-exposure to piperonyl butoxide (PBO) in the WHO adult bioassay and MFOs enzyme microassay reduced the LT50 values and reduced the mean optical density of elevated oxidase activity (0.28-0.42) at 630nm. The LC50 or LT50 values and the level of oxidases were significantly correlated (r=0.825; p<0.05). This study confirmed the presence of permethrin resistance in these mosquito populations. Â© 2010 Korean Society of Applied Entomology, Taiwan Entomological Society and Malaysian Plant Protection Society.